Ultrasound‐Guided Fasciotomy for Anterior Chronic Exertional Compartment Syndrome of the Leg. (9th March 2016) - Balius, Ramon; Bong, David A.; Ardèvol, Jordi; Pedret, Carles; Codina, David; Dalmau, Antonio
Abstract : Chronic exertional compartment syndrome is characterized by exertional pain and elevated intracompartmental pressures affecting the leg in physically active young people. In patients who have failed conservative measures, fasciotomy is the treatment of choice. This study presents a new method for performing fasciotomy using high‐resolution ultrasound (US) guidance and reports on the clinical outcomes in a group of these patients. Over a 3‐year period, 7 consecutive patients with a total of 9 involved legs presented clinically with anterior compartment chronic exertional compartment syndrome, which was confirmed by intracompartmental pressure measurements before and after exercise. After a US examination, fasciotomy under US guidance was performed. Preoperative and postoperative pain and activity levels were assessed as well as number of days needed to "return to play." All patients had a decrease in pain, and all except 1 returned to presymptomatic exercise levels with a median return to play of 35 days.